EVALUASI PERHITUNGAN METODE PAVEMENT CONDITION INDEX (PCI) STUDI KASUS JALAN RAYA LETNAN SUKARNA KECAMATAN CIAMPEA KABUPATEN BOGOR - Muhamad Bagus Santri Aji; Muhammad Nafhan Isfahani (FTSP Universitas Jayabaya, 2022)
Ciampea sub-district is one of the sub-districts with a fairly large population density in the Bogor Regency area, and again every year the population in this district always increases. An increase in population will of course also have an impact on an increase in traffic volume, with an increase in traffic volume which will certainly affect the strength and lifespan of the sidewalk structure. Handling is important, considering the road that has been built, if without proper maintenance and repair it will cause fatal damage, thus requiring pavement reconstruction. From the survey results of arterial roads in Cibungbulang district, the following conditions were obtained: Road conditions Sta 0+000 – Sta 0+100 Good with a PCI value of 61.5, Sta 0+100 – Sta 0+200 are Fair with a PCI value of 45.2 , condition sta 0+200 - Sta 0+ 300 is good with a PCI value of 60, condition Sta 0+3 00 - Sta 0+400 is Fair with a PCI value of 51, Sta 0+400 - Sta 0+500 is Fair with a PCI value of 42 , Sta 0+500 - Sta 0+ 600 very good with a PCI value of 90, Sta condition 0+600 - Sta 0+700 is Fair with a PCI value of 52, Condition sta 0+700 - Sta 0+800 is Fair with a PCI value of 46.2 , Sta 0+800 - Sta 0+900 Very good with a PCI value of 78.1, Sta 0+900 - Sta 1+0 00 good with a PCI value of 64, Sta 1+1 condition 00 - Sta 1 +200 very good with a PCI value of 95.5, condition of Sta 1+200 - Sta 1+300 is very good with a PCI value of 86. Based on processed data obtained at Sta 0+000 - Sta 0+500 rehabilitation is carried out, Sta 0+500 - Sta 0+600 is carried out Routine Maintenance, Sta 0 +600 - Station 0+800 done n Rehabilitation, Sta 0+800 - Sta 0+900 is carried out Periodic Maintenance, Sta 0+900 – Sta 1+1 00 Rehabilitation is carried out, Sta 1+100 – Sta 1+300 is carried out Routine Maintenance.